1986
DOI: 10.1161/01.res.58.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Physiological concentrations of epinephrine potentiate thromboxane A2 release from platelets in the isolated rat heart.

Abstract: The isolated rat heart perfused with washed platelets was used as a model to examine platelet-vessel wall interactions. Release of prostacyclin and thromboxane A2 was measured, using a cascade of smooth muscle bioassay tissues or radioimmunoassays of the stable hydration products. In hearts perfused with rabbit or human platelets, injection of sodium arachidonate caused release of both prostacyclin and thromboxane A2. In hearts perfused with aspirin-pretreated platelets, arachidonate released only prostacyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Following antiplatelet serum there was a prompt fall in platelet count from 625 +31 xlO 9 1" 1 to 80± 0-6 xlO'T 1 at 5 min (99% reduction, P< 0-0001), and thereafter the platelet count remained markedly depressed for more than 100 min (Fig. 1).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Following antiplatelet serum there was a prompt fall in platelet count from 625 +31 xlO 9 1" 1 to 80± 0-6 xlO'T 1 at 5 min (99% reduction, P< 0-0001), and thereafter the platelet count remained markedly depressed for more than 100 min (Fig. 1).…”
Section: Resultsmentioning
confidence: 89%
“…Catecholamines are known to cause platelet activation' 9 ' and, in high concentrations, to cause myocardial necrosis. Kammermeier and Ober" 0 ' observed that this catecholamine effect appears to be dependent on the presence of circulating platelets.…”
Section: Introductionmentioning
confidence: 99%
“…In the isolated rat heart perfused with washed platelets following the Langerdorff 's technique, adrenaline infusion at concentrations within the physiological range potentiates the arachidonate-induced release of TXA 2 without inducing platelet aggregation [277]. Adrenaline infusion at rates determining blood levels achievable in physiological conditions of sympathoadrenal activation (over 4 nmol L ÿ 1 ) influences both the number of circulating platelets and the platelet function [136,[278][279][280][281].…”
Section: In Vivo Catecholamine Effectsmentioning
confidence: 99%
“…Recently in our laboratory it has been found that infusion of adrenaline and other catecholamines in rat isolated hearts, greatly potentiates the release of thromboxane A2 from platelets perfused through the heart (Purchase et al, 1985). We set out to study whether nicotine would also produce this effect via endogenous catecholamine release in vivo.…”
Section: Introductionmentioning
confidence: 99%